Effect of Strain Path on Retained Austenite Transformation Rates and Material Ductility in Transformation-Induced Plasticity-Assisted Advanced High-Strength Steel - Parker Gibbs; Derrik Adams; David T. Fullwood; Eric R. Homer; Anil K. Sachdev; Michael P. Miles (Journal of Manufacturing and Materials Processing)
TBF 1180 steel was plastically deformed under different strain paths in order to study both the ductility and RA transformation rates. Specimens were prepared from a 1 mm thick sheet and then tested incrementally under uniaxial tension, plane-strain tension, and biaxial tension. The retained austenite (RA) levels were measured, as a function of the plastic strain, using electron backscatter diffraction (EBSD). The plane-strain tension specimens had the fastest rate of RA transformation as a function of strain, followed by uniaxial tension, and then biaxial tension. The forming limits were measured for each strain path, yielding major limit strains of 0.12 under uniaxial tension, 0.09 under plane-strain tension, and 0.16 under biaxial tension. These results were compared to prior work on a 1.2 mm Q&P 1180 steel sheet, which had a similar yield and ultimate tensile strength, but exhibited slightly greater forming limits than the TBF material. The visual inspection of the micrographs appeared to show an equiaxed RA morphology in the Q&P 1180 steel and a mixture of equiaxed and lamellar RA grains in the TBF 1180 steel. However, the statistics generated by EBSD revealed that both alloys had RA grains with essentially the same aspect ratios. The average RA grain size in the Q&P alloy was found to be about three times larger than that of the TBF alloy. As such, the small but consistent formability advantage exhibited by the Q&P 1180 alloy along all three strain paths can be attributed to its larger average RA grain size, where larger RA grain sizes correlated with a more gradual transformation rate.